Different Polymorphisms of Vascular Endothelial Growth Factor Gene in Patients with Pre-Eclampsia among The Iranian Women Population - Rana Niktalab (International Journal of Fertility and Sterility, 2020)
Background Pre-eclampsia (PE) is a pregnancy complication and one of the leading causes of maternal and neonatal morbidity and mortality in the world. PE is characterized by high blood pressure and signs of damage to the other organs, most often the liver and kidneys. Given the importance of mutation in the vascular endothelial growth factor (VEGF) gene and its correlation with the incidence of PE, the relationship of VEGF encoding gene polymorphisms rs922583280, rs3025040 and rs10434 with the incidence of PE in the population of Iranian women was studied, in this research. Materials and Methods In this case-control study, 100 pregnant women with PE diagnosis and 50 healthy pregnant women were evaluated using Sanger sequencing method to determine genotypes rs922583280, rs3025040 and rs10434. Results There was no significant difference in the allele frequency of rs922583280 and rs3025040 polymorphisms between case and control groups (P > 0.05), while frequency of the recessive allele (G) for rs10434 polymorphism was significantly higher in the case group compared to the control group (P=0.014, case=24%, control=12%). Frequency of the allele A in the control group was higher than the patient group (case=76%, control=88%). Frequency of AG genotype in the patient group was also higher than the control group. In addition, frequency of AA genotype in the control group was higher than the patient group (case=57%, control=78). Conclusion The results of this study demonstrated a significant difference between patient and control groups for the VEGF coding gene polymorphism rs10434 and it can affect the incidence of PE among Iranian women.